Synthesis and characterization of polyaniline-graphene quantum dots and their potential for Pyrene detection using photoluminescence spectroscopy - Beygisangchin, Mahnoush; Rashid, Suraya Abdul; Shafie, Suhaidi; Kamarudin, Siti Kartom (Springer Science and Business Media B.V., 2024)
The detection of Pyrene, a toxic polycyclic aromatic hydrocarbon, is crucial for environmental monitoring due to its negative impacts on health and ecosystems. While photoluminescence (PL) spectroscopy holds promise for Pyrene detection, its current application is limited. This research aimed to address this gap by developing a novel PL spectroscopy method for Pyrene detection. The method utilizes a simple, low limit of detection (LOD), affordable, rapid, and user-friendly approach. A polyaniline-graphene quantum dot (PANI-GQD) nanocomposite film was synthesized as the sensing layer. For comparison, PL spectroscopy measurements were also taken using GQD and PANI alone. The fabricated thin films were thoroughly characterized using various techniques (FT-IR, UV–Vis, Raman, XRD, FE-SEM, EDX, TGA) to analyze their chemical, optical, physical, and structural properties. The developed PANI-GQD nanocomposite film-based PL spectroscopy successfully detected Pyrene concentrations ranging from 0.001 to 10 × 10–9 mol L−1. Notably, the method achieved an outstanding LOD of 0.40 × 10–9 mol L−1 (S/N = 5) for low-concentration Pyrene detection, surpassing previous limitations. This LOD is well within the WHO's set standards for Pyrene in aquatic environments (3.461 × 10–9 mol L−1). Overall, this research presents a valuable tool for detecting toxic materials relevant to environmental monitoring, with potential for significant socio-economic impact.